2020
DOI: 10.1002/celc.202000615
|View full text |Cite
|
Sign up to set email alerts
|

Electrochemically Generated Interfacial pH Change: Application to Signal‐Triggered Molecule Release

Abstract: Electron transfer processes during redox reactions are frequently accompanied with protonation/deprotonation processes, thus changing H+/OH− concentrations. When the redox reactions proceed at electrode surfaces, being electrochemically processed, changes in local interfacial pH are possible, particularly when the electrolyte solution is not strongly buffered. The pH gradient can be produced in the diffusion layer and its thickness depends on the rate of electrochemical process, which is measured as the curren… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
17
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

5
2

Authors

Journals

citations
Cited by 19 publications
(17 citation statements)
references
References 95 publications
(125 reference statements)
0
17
0
Order By: Relevance
“…The use of the pH-switchable reversible complex formation of the nitro-avidin-biotin or avidin-iminobiotin systems can further benefit from another research direction, which provides reversible pH changes near electrode surfaces upon performing some electrochemical reactions. 26 The local (interfacial) pH change has been already used to control electrochemically activity of surface-immobilized enzymes 27 and to release molecular loads bound to an electrode surface, 28 particularly with pH-degradable covalent bonds. 29 The present paper reports on the use of electrode-surface immobilized nitro-avidin or avidin in combination with biotinylated or iminobiotinylated substances, respectively, with the local pH changes produced electrochemically.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The use of the pH-switchable reversible complex formation of the nitro-avidin-biotin or avidin-iminobiotin systems can further benefit from another research direction, which provides reversible pH changes near electrode surfaces upon performing some electrochemical reactions. 26 The local (interfacial) pH change has been already used to control electrochemically activity of surface-immobilized enzymes 27 and to release molecular loads bound to an electrode surface, 28 particularly with pH-degradable covalent bonds. 29 The present paper reports on the use of electrode-surface immobilized nitro-avidin or avidin in combination with biotinylated or iminobiotinylated substances, respectively, with the local pH changes produced electrochemically.…”
mentioning
confidence: 99%
“…It has been already shown that the electrochemical reduction of O 2 results in pH increase near an electrode surface. 26,28 Indeed, the electrochemical oxygen reduction leading to H 2 O 2 or H 2 O production (depending on the potential applied and the electrode material) results in consumption of H + ions, thus, producing the H + depletion near the electrode surface and the pH increase. This results in the dissociation of the nitro-avidin-biotin complex and release of the biotinylated fluorescent dye, then detected in a bulk solution by fluorescence measurements.…”
mentioning
confidence: 99%
“…Many (bio)-electrochemical processes have been investigated and exploited to develop (bio)-electrochemical sensors, biofuel cells (or energy harvesting devices) and signal-triggered devices (e. g., stimuli responsive electrodes, etc.). [1][2][3][4] Some of the redox reactions, previously regarded as (bio)-electrochemical processes, are accompanied by protons production/consumption, [5][6][7] inducing a pH gradient (ΔpH) that propagates perpendicularly from the electrode surface within the diffusion layer, as displayed in Figure 1. The thickness of the pH gradient is generally affected by the rate of the electrochemical process (measured as a current density), rate of H + /OH À ion diffusion, and buffer concentration (or ionic strength).…”
Section: Introductionmentioning
confidence: 99%
“…However, the previous studies did not address the effect of buffer concentration on the thickness of the local layer with the changed pH. This dependence is highly important for many practical applications, particularly when the depletion layer is used for actuating processes resulting in (bio) molecule release [7] or variation of (bio)catalytic activity near an electrode surface. [5] Herein, we demonstrate the possibility for operando quantification of the thickness of the layer where pH changes are occurring.…”
Section: Introductionmentioning
confidence: 99%
“…One of the powerful approaches to the kinetic control of biocatalytic processes, particularly for surface-immobilized enzymes, is based on changes in local (interfacial) pH values. The local pH changes can be stimulated by different methods, particularly upon electrochemical reactions resulting in the consumption or release of H + cations, thus generating local pH on an electrode surface different from the pH in a bulk solution . Because many enzymes have a strong dependence of the reaction rates on the surrounding pH value, the activity of the electrode-immobilized enzymes can be switched or tuned by applying electrical potentials on the modified electrode, resulting in the generation of a local pH different from the original bulk pH value (Figure A) .…”
Section: Introductionmentioning
confidence: 99%